Self-referral practice among patients attending outpatient department of Northwest Comprehensive Specialized Hospital, Ethiopia: a multi-center cross-sectional study - Alemu, Tihtna; Yigzaw, Zeamanuel Anteneh; Alemu, Mekides Engeda; Asmare, Lakew (Frontiers in Public Health, 2025)
BackgroundIn resource-scarce countries such as Ethiopia, patients coming from primary care facilities directly to specialist hospitals pose an enormous challenge to the health system. This practice hinders continuity of care and reduces the quality of healthcare. However, little is known about the prevalence of self-referral in Ethiopia. Therefore, this study aimed to assess the self-referral practice and its associated factors in Northwest Comprehensive Specialized Hospital, Ethiopia.MethodsA multi-center institutional-based cross-sectional design was conducted. A systematic random sampling technique was used to recruit a total of 446 participants. Structured interviewer-administered questionnaires were used. The collected data were entered into EpiData software and exported for analysis. Variables with a p-value of <0.25 in the bi-variable analysis were considered candidates for multivariable analysis. A p-value of <0.05 and a 95% confidence interval were used to determine the statistical association.ResultsThe prevalence of self-referral practice was 339 (70.40%). Thus, respondents who had an education level of college and above [AOR = 0.35, 95% CI = 0.10, 0.92], respondents who perceived their illness [AOR = 1.11, 95% CI = 1.06, 2.53], and those who had adequate knowledge about the referral system (AOR = 0.31, 95%CI = 0.16, 0.68) were significantly associated variables with self-referral practice.ConclusionAccording to this study’s findings, more patients than expected visited specialized hospitals than previously reported. Various factors, such as educational level, perceived severity of illness, confidence in laboratory services, lack of information about referral methods, and limited use of primary care, contribute to this issue. Addressing these factors and strengthening the referral process are important steps to improve healthcare delivery, continuity of care, and patient satisfaction in Ethiopia.